Pengembangan Kartu Kendali Praktik Pada Program Studi Pendidikan Tata Busana - Rengganingsih, Asri; Sawitri, Sicilia (Fashion and Fashion Education Journal, 2021)
Discipline in learning is very important, as is the case for students in the Fashion Education Study Program who take practical courses. The establishment of discipline in the learning process requires efforts from the instructor as well as students themselves, so an evaluation tool in the form of a practice control card needs to be prepared. The practice control card is an evaluation tool used to monitor the progress of student practice learning. The purpose of this study was to produce a valid practice control card product as an evaluation tool in the Fashion Education Study Program. By which Research and Development method, this research was conducted. The development procedure goes through six stages, namely potential and problem analysis, data collection, product design, product validation, product revision, and product trials. The instrument used was a practice control card validation sheet and student assessment questionnaire, with validity testing using the Aiken V formula and reliability testing using rating formulas. Data analysis used quantitative descriptive methods with percentages. The results of the study indicate the level of validity of the practice control card in the valid category, namely the validity test by experts obtained by 90% and the assessment of students obtained 84% results. The conclusion of this research was the practice control card is declared valid as a learning evaluation tool in the Fashion Education Study Program. Suggestions that could be submitted are for researchers who want to conduct similar research, could conduct up to test the effectiveness of the use of practice control cards.